PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP PROFESIONALISME GURU PAUD DI KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Choiriyah Ulfah; Yovitha Yuliejantiningsih; Soegeng Soegeng (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2016)
The purposes of this study are: (1) to determine the influence of compensation on the professionalism of early childhood teachers in the District of West Ungaran, Semarang Regency; (2) to determine the effect of working motivation in the professionalism of early childhood teachers at the District of West Ungaran, Semarang Regency; (3) to determine the effect of compensation and motivation to work together in the professionalism of the early childhood teachers in the District of West Ungaran, Semarang Regency.The populations of this study are the early childhood teachers who were in the District of West Ungaran Semarang regency as many as 298 people’s with samples taken proporsionate stratiefied random sampling as many as 161 people. The methods of data collection use questionnaires. Analysis of the data used is descriptive analysis, test requirements and test hypotheses. Hypothesis test use simple regression analysis and multiple regression analysis. To analyze the data use SPSS for Windows 21.The results shows that the average of acquisition score is 95.22 professionalism of teachers including professional enough categories, the average acquisition score a compensation of 59.51 medium category, and earned an average score of 75.58, including work motivation medium category. The test results prerequisite research data were normally distributed, linear and does not occur multikolinieritas. Hypothesis tests found to contain a significant influence on the professionalism of teachers represented by the equation of Y = 70.090 + 0424 X1; the strength of correlation of 0.704 with a contribution of 0,496 or 49.6%. A significant difference in the professionalism of teachers' motivation to work with the equation of Y = 24.383 + 0.937 X2; the strength of correlation of 0.682 with a contribution of 0.464 or 46.4%. Compensation and motivation significantly influential work together in the professionalism of teachers represented by the equation of Y = 38.376 + 0.274 X1 + 0.538 X2; the strength of correlation of 0.766 with a contribution of 0.586 or 58.6%.